Veillonella dispar bacteremia in an elderly patient with urothelial carcinoma: a case report and literature review - Gupta, Harshit; El Ayoubi, Wassim; Huerta III, Nicholas H.; Naqvi, Haider A. (International Journal of Research in Medical Sciences, 2025)
Veillonella is a genus of Gram-negative anaerobic cocci. Veillonella is typically benign and a normal part of the intestinal and genitourinary flora, however in the presence of certain risk factors such as intravenous drug abuse, malignancy, and immunosuppression, some species belonging to this genus have been reported to cause severe deep-seated infections. Veillonella dispar is one of the three subgroups of Veillonella species associated with deep-seated human infections. V. dispar is reported to be associated with very few diseases, including infective endocarditis, vertebral osteomyelitis, and bacteremia. In this case report, we discuss the case of 89-year-old male with a history of transurethral resection of a bladder tumor who presented with fever, burning micturition, and decreased urine output who was later diagnosed with V. dispar bacteremia during his hospitalization, making it the fifth report of bacteremia in the literature. Additionally, we provide a brief literature review on V. dispar infections in humans.